USING NANOCLAY HYDROPHILIC BENTONITE AS A FILLER TO ENHANCE THE MECHANICAL PROPERTIES OF ASPHALT - Asim Mohammad Hussain, Wail; Thamer Abdulrasool, Abdulrasool; N Kadhim, Yasir (Journal of Applied Engineering Science, 2022)
Higher traffic loads on the wheels, increased traffic volumes, and exposure to changing weather conditions result in increasing the road stresses and strains, putting the paving layers in danger of degradation such as fatigue, stripping, cracking, and rutting. A tremendous number of studies and trials have been conducted to modify asphalt to have a longer service life, less maintenance, be cheaper, and be more environmentally friendly. Recently, nanotechnology has proven very beneficial in all industries, including asphalt. It can be used to enhance the asphalt's mechanical properties. Using nano clay in asphalt is expected to improve the mechanical properties and the service life of the asphalt. So the main objective of this study is to investigate the performance of nano clay hydrophilic bentonite in improving the physical characteristics of asphalt concrete. This study uses nano clay with various replacement ratios as fillers to the ordinary used limestone filler in asphalt concrete. The used replacement percentages were (0%, 20%, 40%, 60%, 80%, and 100). The experimental tests that were conducted in this study include Marshall Stability (MS), Marshall Flow (MF), voids in mineral aggregate (VMA), theoretical maximum specific gravity (Gmm) and air voids (AV).The results showed a noticeable enhansment in the behavior of the asphalt mix with increasing the replacement percentage by nanoclay. Also, it was found that the 60% replacement rate by nanoclay has the highest Marshall stability with an increase of 93%, also the lowest flow with a decrease of 25% compared to the control asphalt mix.
Keywords: nanoclay, filler, asphalt, nanotechnology, mechanical properties